Lathrolestes clypeatus Zetterstedt 1838 ... - Reshchikov, Alexey (Zenodo, 2015)
Lathrolestes clypeatus (Zetterstedt, 1838) Figs. 19, 21, 31, 61, 62. Tryphon clypeatus Zetterstedt, 1838: 399. Holotype ♀, MZLU [examined]. Type locality: Sweden (Lapland). Lathrolestes eriocraniae Seyrig, 1928: 201. Holotype ♀, MNHN [not examined]. Type locality: France. Material. 2♀, DENMARK, Strandmølle, Boserup, ZMUC; 3♂, DENMARK, Sjaelland, Korsør, ZMUC; 1♀, FINLAND, Lappland, Enontekis, mt. Saana, 27.vi.1962, leg. K.Åhman, (ZMUT, Jussila coll.); 1♀, FINLAND, Lappland, mt. Siilaskoski, 27.vi.1962, leg. K.Åhman, (ZMUT, Jussila coll.); 1♀, FINLAND, Turku, Paattinen, Krouvintie, 92 6787:3244, Malaise trap, 1– 31.5.2004, leg. R. Jussila leg., (ZMUT, Jussila coll.); 1♀, NORWAY, Troms, Storfjord, Skibotn, 29.vi.1962, leg. M.Meinander, (ZMUT, Jussila coll.); 1 ♀, NORWAY, Sør-Trøndelag, Oppland, Kongsvoll, Raubekken, 900m., Øvre, Malaise trap, 03.VII.1980, leg. J. O. Solem, (NTNU); 1♀, NORWAY, Hedmark, Stor-Elvdal, Solbakken, Malaise trap, 24.VI.1986, leg. E. Stur, (NTNU); 1♀, NORWAY, Akerhus, Fetsund, Asak ... : Published as part of Reshchikov, Alexey, 2015, Review of North European species of the genus Lathrolestes (Hymenoptera, Ichneumonidae) with description of one new species from Öland (Sweden), pp. 1-47 in Zootaxa 4033 (1) on pages 18-19, DOI: 10.11646/zootaxa.4033.1.1, http://zenodo.org/record/289776 ...